Experiment and Application Study on High-Performance Grouting Material Used to Solve the Floor Heave Problem of Broken Soft Rocks - Xu, Jie; Jiang, Jingdong (Frontiers in Physics, 2022)
To meet the project demands of controlling the floor heaves in broken soft rocks, a new high-performance grouting material was studied. The main performance parameters of the grouting materials with different ratios, such as the setting time, the density and bleeding ratio, the viscosity, and fluidity, were investigated in the laboratory tests. The results indicated that the optimal additive ratio is 6‰. The unconfined compression strength tests and conventional triaxial compression tests were carried out on the common and reinforced mudstones, which indicate that the strengthened effect of the new grouting materials is significant. The new high-performance grouting material was applied to controlling the floor heaves of the broken soft rocks in the coal mine. The numerical simulation and filed monitoring results indicate that the new grouting material can effectively improve the strength of soft rock and control the floor heaves.